Strategies and Challenges of Developing Leaders for a Modern Day Armed Forces (The Shivapuri Journal, 2026)
In an age of rapid technological advancement and fluid nature of contemporary security environment, developing agile, ethically tuned and professionally sound military leaders has become a strategically imperative for modern day armed forces globally. This article presents a comprehensive analysis on the paradigm shift in developing military leader’s arguing that operational success in contemporary volatile, uncertain, complex and ambiguous (VUCA) security environments gratifies a decisive move from industrial age, hierarchical command models toward cohesive and adaptive leadership development frameworks. These frameworks must combine continuous academic education, deliberate experiential learning, structured mentorship program and technology enabled training modules synergistically. The argument based analysis identifies resolute institutional challenges which includes doctrinal aspects, cultural inertia, and existing disparities in the defence resources. Fundamentally, it employs a qualitative, multi method research design to analyze the strategies and challenges in developing military leaders for modern day armed forces. It concludes with targeted, evidence based recommendations emphasizing the need for self-motivated, ethically sound curriculum and progressive spirited learnings with particular focuses in the militaries from the South Asian countries.